Growth-Promoting Effects of Thiamethoxam on Sugarcane Ripened With Sulfometuron-Methyl - de Paula Silva, Deise; Jacomassi, Lucas Moraes [UNESP]; Oliveira, Josiane Aparecida Viveiros [UNESP]; Oliveira, Marcela Pacola [UNESP]; Momesso, Letusa [UNESP]; de Siqueira, Gabriela Ferraz [UNESP]; Foltran, Rodrigo [UNESP]; Soratto, Rogério Peres [UNESP]; Dinardo-Miranda, Leila Luci; Crusciol, Carlos Alexandre Costa [UNESP] (Springer Nature, 2022)
One of the biggest challenges in the sugarcane industry is obtaining raw material of sufficiently high quality to ensure best economic return. The use of technologies such as chemical ripeners to increase sucrose accumulation is highly recommended when natural ripening conditions are unsatisfactory. The insecticide thiamethoxam is also a bioactivator that can stimulate new stalk and leaf growth, and thus the application of thiamethoxam to sugarcane ratoon regrowth in association with ripener may improve sugarcane quality and yields. This study aimed to evaluate the effectiveness of foliar application of thiamethoxam to sugarcane ratoon regrowth alone or in association with the ripener sulfometuron-methyl. The study comprised six experiments carried out in the early and late harvest seasons in three different locations using the sugarcane varieties RB855453 and SP80-3280. The treatments consisted of a control (natural ripening), application of the ripener sulfometuron-methyl or the bioactivator thiamethoxam alone, or application of both ripener and bioactivator. Thus, biometric and technological parameters were evaluated. The use of thiamethoxam increased stalk yield significantly, with gains up to 13 Mg ha−1. When both ripener and bioactivator were applied, sugar yield increased by up to 14.7% compared with the control. As a bioactivator, thiamethoxam has the potential to increase energy cogeneration from sugarcane via higher biomass production. Thus, thiamethoxam application on sugarcane regrowth treated with sulfometuron-methyl promoted desirable effects on the plant physiology without altering the industrial quality of the sugarcane juice.
Keywords: Bioactivator; Phytotonic effect; Productivity; Ripener; Saccharum spp